Interfacing high-performance liquid chromatography and cold-vapour atomic absorption spectrometry with on-line UV irradiation for the determination of organic mercury compounds - Falter, Ralf; Schöler, Heinz Friedrich (Journal of chromatography, 1994)
A liquid chromatographic method with on-line UV irradiation was developed for the determination of organic mercury compounds by cold-vapour atomic absorption spectrometry (AAS). Methyl-, ethyl-, phenyl- and inorganic mercury were separated on R.P C18 columns. An UV-irradiation lamp was used for the on-line destruction of the organomercury compounds. Sample and NABH4 solution were continuously fed to the reaction vessel where mercury was reduced. The volatilized mercury was swept into the absorption cell of a cold-vapour AAS system by nitrogen. The detection limit for methylmercury is 80 pg absolute (S/N = 3).